Impact of E-Wallets on Consumer Spending Behavior: A Mediating Role of Financial Management - Mahato, Surendra; Yadav, Ranju; Mahato, Bijay (Journal of Economics and Management, 2025)
The study explores the effects of e-wallets on consumer spending through financial management in an urban environment of Nepal. The research has employed a positivism philosophy and quantitative approach. Based on Technology Acceptance Model (TAM), it analyzed characteristics such as attitudes, subjective norms and perceived behavior control with six-point Likert scale responses. Primary data was collected through a well-structured questionnaire from a sample was 400 adults who used the platforms of Khalti, eSewa and IME Pay. The key constructs were perceived usefulness (PU), perceived ease of use (PEOU), perceived security (PS) as the predictors, financial management (FM) as the mediating variable and consumer spending behavior (CSB) as the dependent outcome. Statistical tests (correlations, the multiple regression model, and mediation) showed that PU, PEOU, and PS had significant effects on FM and CSB with PS as the most potential factor. This was because, FM also had a direct and positive influence on CSB and mediated the relationships amid the three predictors and spending outcomes. These results empirically extend TAM by illustrating how TAM can be applied in post-adoption behaviors, showing that e-wallets are not solely used as transaction tools, but as a means of enabling financial responsibilities. Such findings have implication for fintech providers who should improve on ease of use, security and budgeting functions as a wake-up call. And this should also be borne in mind by policy-makers concerned with ensuring safe and customer-oriented digital financial spaces.